SIMULATOR ALAT MUSIK TRADISIONAL CALEMPONG PADA PLATFORM ANDROID - Novi Yanti; Diki Arisandi; Liza Trisnawati; Weli Andrian (Universitas Harapan Medan, 2020)
Indonesia is the largest archipelago country in the world. The islands are stretching from Sabang to Merauke, which causes Indonesia rich in ethnicity, language, religion, and culture. One of them is a traditional art in the Kampar Regency that will use in every celebration of holidays, namely calempong. Calempong instruments are often seen in performances at weddings. The concept of this research is to create and combine the technology with traditional musical instruments through the hardware or software, and delivering an interesting learning experience of musical instruments. This simulator is presented in 3D by using unity software and Blender 3D, and embedding the Kampar song so that it does not eliminate the local cultural values.